PENINGKATAN HASIL BELAJAR TEMATIK TERPADU MENGGUNAKAN MODELCOOPERATIVELEARNING TIPE CRH DI SD - Sari, Surtika; Sri Lena, Mai (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
This study aims to determine the improvement of integrated thematic learning outcomes using the CRH Cooperative Learning model. This research is a classroom action research that uses qualitative and quantitative approaches. The subjects used in this study consisted of teachers and 32 students. This research was conducted 2 cycles. Cycle I was held for 2 meetings and cycle II was held for 1 meeting, with four stages, namely planning, implementation, observation and reflection. The results of this study are : the percentage observations of RPP in the first cycle, 78 % increased in the second cycle, 95 % . The result of observation of teacher aspect in cycle 1,78,75% increased in cycle II, 92,5%. The results of the observations of students in the first cycle, 81.25 % increased in the second cycle, 92.5%. Student learning outcomes in the first cycle, 67,18% (C) increased in the second cycle 92,4% (SB).